Acupuncture-Associated Mycobacterium goodii Infection of Prosthetic Knee Joint. Issue 1 (January 2019) - Kruse, Jason P.; Lewis, Roshan J.; Smith, Hayden L.; Taylor, Matthew J.
Abstract : Abstract: Mycobacterium goodii is rarely associated with prosthetic joint infections. We report a case of M. goodii septic arthritis in an adult with a prosthetic knee–associated diagnosis subsequent to acupuncture. In patients with prosthetic joint replacements receiving acupuncture therapy, one should consider avoiding insertions near these joints.